The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.4103/1673-5374.374140
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of glial cells to the neuroprotective effects triggered by repetitive magnetic stimulation

Abstract: Repetitive transcranial magnetic stimulation has been increasingly studied in different neurological diseases, and although most studies focus on its effects on neuronal cells, the contribution of non-neuronal cells to the improvement triggered by repetitive transcranial magnetic stimulation in these diseases has been increasingly suggested. To systematically review the effects of repetitive magnetic stimulation on non-neuronal cells two online databases, Web of Science and PubMed were searched for the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Our findings align with previous studies in healthy rodents, where authors reported no changes in microglia and astrocyte reactivity after 3 and 5 sessions of high and low frequency rTMS stimulation [ 10 , 11 , 65 ]. In contrast, in rat models of spinal cord injury and chronic pain and depression, rTMS decreased microglia activation and inflammatory markers after 8 and 4 weeks of daily rTMS [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings align with previous studies in healthy rodents, where authors reported no changes in microglia and astrocyte reactivity after 3 and 5 sessions of high and low frequency rTMS stimulation [ 10 , 11 , 65 ]. In contrast, in rat models of spinal cord injury and chronic pain and depression, rTMS decreased microglia activation and inflammatory markers after 8 and 4 weeks of daily rTMS [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in rat models of spinal cord injury and chronic pain and depression, rTMS decreased microglia activation and inflammatory markers after 8 and 4 weeks of daily rTMS [ 66 , 67 ]. This discrepancy might suggest that rTMS modulates microglia activity when it is already in an active state and might have no effects when delivered in healthy subjects, as indicated in a recent literature review [ 65 ]. Alternatively, discrepancy of results might stem from differences in the study design, such as the subject brain size and stimulated areas (non-human primate versus rodent brain size), or the number of stimulation sessions (3 weeks of stimulation delivered in the current study versus the 4 and 8 weeks of delivery by [ 66 , 67 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glial cells, primarily astrocytes, regulate the quantities of extracellular glutamate ( Fan et al, 2023 ; Liu et al, 2023 ; Ferreira et al, 2024 ). Figure 3 illustrates and discusses the conceivable mechanism of MSG-induced neurotoxicity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is a technology that stimulates and identifies changes in the direction of the proton rotation axis that appear in the water that makes up the tissues of the organism [62,63]. Briefly, MRI uses magnets with a large magnetic field that drives the protons in the body to align with the field produced [64]. The protons are stimulated and fight against the strength of the magnetic field and when the radiofrequency field is turned off the protons align with the magnetic field and the sensors can identify the energy released.…”
Section: Insights From Neuroimaging On Exercise and Nutrition's Impactmentioning
confidence: 99%